Analysis and Warning Model of Logistics Risks of Cross-Border E-Commerce - Weizhe Mu (Discrete Dynamics in Nature and Society)
Logistics is a key aspect of cross-border e-commerce (CBEC). If any link of logistics fails, the outcome of CBEC may fall shortage of expectation. Logistics risks are now major bottlenecks of CBEC development. Therefore, it is important to study CBEC logistics risks. This paper divides CBEC logistics risks into environmental risks, management risks, operation risks, and clearance risks and establishes a Bayesian model to warn CBEC logistics risks. Then, GeNIe software was employed to simulate the model, and an empirical analysis was conducted through forward prediction and reverse diagnosis. The results help enterprises to intuitively identify risk reducers, formulate effective risk control schemes, and thereby reduce CBEC logistics risks.